Ozone therapy as adjuvant treatment in patients with COVID-19 (Research, Society and Development, 2021)
The new SARS-CoV-2 coronavirus was officially reported in December 2019 in China. Transmission of the virus is by direct and indirect contact, and there are reports of symptomatic and asymptomatic people. It covers serological test, rapid test, testing of blood and respiratory samples as diagnosis. The recommended preventive measures include hand washing, use of alcohol, use of masks, cleaning of surfaces, isolation for positive or exposed people, and the search for complementary measures, such as the use of ozone therapy. Ozone O3 is composed of three oxygen atoms, and is a viable ally as an adjuvant for the treatment of COVID-19, because it has an oxidizing active that decreases the possible complications due to lung inflammation. It has been shown to be beneficial as a disinfectant and sterilizer for medical instruments and environments. This work aims to show the benefits of ozone, and its efficacy as an aid in the treatment of coronavirus. A review of narrative literature on the subject was carried out, using as reference bases articles available in online platforms such as Pubmed and Scielo, in English and Portuguese (Brazil), where the use of the most current articles was prioritized. Ozone therapy in combination with other antiviral drugs may be effective and useful in patients with COVID-19. However, it is evident that studies to clarify the utilities of ozone are still needed in order to improve the proposals for protocol and effective therapeutic applications in the treatment of COVID-19.